المؤسسات ا المعلومات في تحسین الأداء المال دور تكنولوج ة المسیلة 􀀝 ة لولا 􀀝 المنطقة الصناع 􀀧 ة الناشطة 􀀝 الاقتصاد - لكحالي, الحاج; بوساق, أمين (جامعة محمد بوضياف المسيلة, 2017)
Summary: The objective of this research is to study the impact of information technology on improving Financial performance. To achieve This objective, we discussed the theoretical concepts and the theoretical foundations related to the approaches related to information technology and Financial performance, while the practical chapter included an examination of the role of IT in improving Financial performance in the companies which were a subject of Our study. The questionnaire has been distributed to a sample consisting of 32 operating in M'sila industrial zone the am of this questionnaire is to test the impact of it tools available in the companies of on single on the Financial performance. the results ston than their a positive impact of IT tools on Financial performance indicators. :
Keywords: Information Technology, Financial Performance, Financial Performance Assessment, Financial Balances Indicators, Financial Ratios.